VIP-Expressing GABAergic Neurons: Disinhibitory vs. Inhibitory Motif and Its Role in Communication Across Neocortical Areas - Apicella, Alfonso junior; Marchionni, Ivan (Frontiers in Cellular Neuroscience, 2022)
GABAergic neurons play a crucial role in regulating and controlling the activity of excitatory neu-rons. Even though GABAergic neurons constitute a small fraction of cortical neurons, their peculiar morphology and functional properties make them an intriguing and challenging task to study. Here, we review the basic anatomical features, the circuit properties, and the possible role in the relevant behavioral task of a subclass of GABAergic neurons that express vasoactive intestinal polypeptide (VIP). These studies were performed using transgenic mice in which the VIP-expressing neurons can be recognized using fluorescent proteins and optogenetic manipulation to control (or regulate) their electrical activity. Cortical VIP-expressing neurons are more abundant in superficial cortical layers than other cortical layers, where are mainly studied. Optogenetic and paired recordings per-formed in ex vivo cortical preparations show that VIP-expressing neurons mainly exert their inhibi-tory effect onto somatostatin-expressing (SOM) inhibitory neurons, leading to a disinhibitory effect onto excitatory pyramidal neurons (PCs). Even though this subclass of GABAergic neurons release their neurotransmitters onto other GABAergic and non-GABAergic neurons, suggesting other possi-ble circuit roles more than a disinhibitory effect. The heterogeneity of VIP-expressing neurons might suggest that these neurons be involved and recruited during different functions, thus inhibit-ing/disinhibiting GABAergic and non-GABAergic neurons at local and distal networks depending on the specific local circuit in which are embedded and possibly on behavioral states of the animal. Although VIP-expressing neurons represent only a tiny fraction of GABAergic inhibitory neurons in the cortex, these neurons' selective activation/inactivation could produce a relevant behavioral ef-fect in the animal. Regardless of the increasing finding and discoveries on this subclass of GA-BAergic neurons, there is still a lot of missing information, and more studies should be done to un-veil their role at the circuit and behavior level in different cortical layers and across different neo-cortical areas.